Convective forces contribute to post‐traumatic degeneration after spinal cord injury - Hoi Y. Kwon; Christopher Streilein; R. Chase Cornelison (Bioengineering & Translational Medicine)
Abstract Spinal cord injury (SCI) initiates a complex cascade of chemical and biophysical phenomena that result in tissue swelling, progressive neural degeneration, and formation of a fluid‐filled cavity. Previous studies show fluid pressure above the spinal cord (supraspinal) is elevated for at least 3 days after injury and contributes to a phase of damage called secondary injury. Currently, it is unknown how fluid forces within the spinal cord itself (interstitial) are affected by SCI and if they contribute to secondary injury. We find spinal interstitial pressure increases from −3 mmHg in the naive cord to a peak of 13 mmHg at 3 days post‐injury (DPI) but relatively normalizes to 2 mmHg by 7 DPI. A computational fluid dynamics model predicts interstitial flow velocities up to 0.9 μm/s at 3 DPI, returning to near baseline by 7 DPI. By quantifying vascular leakage of Evans Blue dye after a cervical hemi‐contusion in rats, we confirm an increase in dye infiltration at 3 DPI compared to 7 DPI, suggestive of higher fluid velocities at the time of peak fluid pressure. In vivo expression of the apoptosis marker caspase‐3 is strongly correlated with regions of interstitial flow at 3 DPI, and exogenously enhancing interstitial flow exacerbates tissue damage. In vitro, we show overnight exposure of neuronal cells to low pathological shear stress (0.1 dynes/cm2) significantly reduces cell count and neurite length. Collectively, these results indicate that interstitial fluid flow and shear stress may play a detrimental role in post‐traumatic neural degeneration.